1983
DOI: 10.1136/bmj.286.6358.16
|View full text |Cite
|
Sign up to set email alerts
|

Increased incidence of malignancy in dermatitis herpetiformis.

Abstract: threshold dose, laser irradiation has an inhibitory effect on tumour growth as opposed to its simple thermal effect. Our experience suggests, however, that this potential '.cure" cannot be achieved in clinical practice. Simple laser irradiation, as opposed to laser irradiation after previous photosensitisation of tumour tissue with haematoporphyrin dye,12 therefore holds little hope of cure except, perhaps, in rare instances of slowgrowing polypoid tumours within the bronchial lumen. Surgery, however, is the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
1
2

Year Published

1984
1984
2004
2004

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(65 citation statements)
references
References 9 publications
5
57
1
2
Order By: Relevance
“…The malignancies were diagnosed at an age when the current types of malignancies in our region are prevalent in about the same or an even higher frequency [26]. Therefore in our material we did not find a higher risk of de veloping malignancies in patients with DH, as has been indicated in other studies [6,7]. Obviously a prospective study is necessary to investigate if DH is associated to malig nancies and if treatment with sulfones, as in dicated by Mansson [6], increases that risk.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…The malignancies were diagnosed at an age when the current types of malignancies in our region are prevalent in about the same or an even higher frequency [26]. Therefore in our material we did not find a higher risk of de veloping malignancies in patients with DH, as has been indicated in other studies [6,7]. Obviously a prospective study is necessary to investigate if DH is associated to malig nancies and if treatment with sulfones, as in dicated by Mansson [6], increases that risk.…”
Section: Discussionsupporting
confidence: 67%
“…Obviously a prospective study is necessary to investigate if DH is associated to malig nancies and if treatment with sulfones, as in dicated by Mansson [6], increases that risk. However, we were not able to confirm the results reported by Leonard et al [7] in a retrospective study of 109 DH patients, showing that the risk of developing a lym phoma increased considerably in DH pa tients. The overall risk for DH patients to develop malignancies does not seem to be dramatic; therefore DH patients should not be overambitiously investigated for suspect ed internal malignancies.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Though there are a number of case reports of the asso ciation of lymphoma and dermatitis herpeti formis [13,[38][39][40], the increased prevalence of lymphoma was only demonstrated re cently [41], It was also claimed that a GFD protected against lymphoma, but both the numbers and methods of selection were inad equate to draw these conclusions. Other ma lignancies have also been described, but no carcinomas of the small intestine have been recorded [41].…”
Section: Dermatitis Herpetiformis and Malignancymentioning
confidence: 99%
“…However an earlier study suggested that non-responders may be at increased risk of developing lymphoma [41], but in this study it was difficult to separate intrinsic non-responders from nonresponders resulting from an underlying lymphoma. It has been claimed that patients with dermatitis herpetiformis who have a similar gluten-sensitive enteropathy and who also have an increased risk of developing malignant lymphoma, can be protected by a gluten-free diet from the development of a lymphoma [46]. The numbers of patients involved and the methods of their selection in this study were totally inadequate to draw such a conclusion.…”
Section: Does a Gluten-free Diet Protect Against The Development Of Lmentioning
confidence: 46%